Addressing Antibiotic Failure—Beyond Genetically Encoded Antimicrobial Resistance - Haney, Evan F.; Hancock, Robert E. W. (Frontiers in Drug Discovery, 2022)
Antibiotic failure can be defined as any clinical situation where treatment with antibiotics fails to cure the patient and remove the infection. Genetically-determined antibiotic resistance certainly contributes to antibiotic failure in the clinic, but this is not the only reason why antibiotics fail and it is likely not the most common cause of antibiotic failure. In this perspective article, we outline several widespread examples of situations where antibiotic treatment fails, even in the absence of formal resistance, including biofilm associated-infections (65% of all infections) as well as infections in sepsis (19.7% of all deaths) and immune compromised individuals. We then discuss various strategies that are being employed to address the issue of antibiotic failure and emphasize that antibiotic failure should be given increased awareness and resources to address this underappreciated but critical issue.